2020
DOI: 10.3892/ijmm.2020.4568
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential canonical 1 channel mediates the mechanical stress‑induced epithelial‑mesenchymal transition of human bronchial epithelial (16HBE) cells

Abstract: Airway remodeling is a central event in the pathology of chronic obstructive pulmonary disease (cOPd) that leads to airway narrowing and subsequently, to increased mechanical pressure. High mechanical pressure can exacerbate airway remodeling. Thus, a treatment regimen aimed at disrupting this high-pressure airway remodeling vicious cycle may improve the prognosis of patients with cOPd. Recent studies have demonstrated that mechanical stress induces lung epithelial-mesenchymal transition (EMT), which is common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…These effects of moderate levels of mechanical cues are in contrast with the upregulation of inflammatory markers reported previously in the context of mechanical ventilation and excessive mechanical stretch and compression 9,18 . Contrary to studies using whole mount tissue 19 , undifferentiated primary cells 20 or cell lines 21,39,43 , our model may have captured phenotype-modulating, potentially even beneficial, effects of normal airflow and stretch by (i) using human primary cells from multiple human donors, (ii) allowing the basal cells to differentiate into a pseudostratified airway epithelium in the presence of mechanical stimulation, and (iii) applying mechanical stimulation over prolonged times, i.e. over 7 days compared to 24-48h 43,44 , in order to capture adaptive remodeling rather than an acute insult.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These effects of moderate levels of mechanical cues are in contrast with the upregulation of inflammatory markers reported previously in the context of mechanical ventilation and excessive mechanical stretch and compression 9,18 . Contrary to studies using whole mount tissue 19 , undifferentiated primary cells 20 or cell lines 21,39,43 , our model may have captured phenotype-modulating, potentially even beneficial, effects of normal airflow and stretch by (i) using human primary cells from multiple human donors, (ii) allowing the basal cells to differentiate into a pseudostratified airway epithelium in the presence of mechanical stimulation, and (iii) applying mechanical stimulation over prolonged times, i.e. over 7 days compared to 24-48h 43,44 , in order to capture adaptive remodeling rather than an acute insult.…”
Section: Discussionmentioning
confidence: 97%
“…Contrary to studies using whole mount tissue 19 , undifferentiated primary cells 20 or cell lines 21,39,43 , our model may have captured phenotype-modulating, potentially even beneficial, effects of normal airflow and stretch by (i) using human primary cells from multiple human donors, (ii) allowing the basal cells to differentiate into a pseudostratified airway epithelium in the presence of mechanical stimulation, and (iii) applying mechanical stimulation over prolonged times, i.e. over 7 days compared to 24-48h 43,44 , in order to capture adaptive remodeling rather than an acute insult. The temporal dynamics, remodeling processes, and heterogeneous responses as observed in our study would likely have been missed in these previously used experimental designs.…”
Section: Discussionmentioning
confidence: 99%
“…Several EMT studies focused on TRP channels and K + channels have been reported ( Table 2 ). Wang et al and Xu et al have revealed that TRP channels, which are non-selective cation channels that transmit not only Na + and K + , but also Ca 2+ and Mg 2+ , are associated with EMT in asthma and chronic obstructive pulmonary disease [ 91 , 92 , 93 ]. TRP channels are widely recognized to respond to temperature, nociceptive stimuli, touch, osmotic pressure, pheromones, and other stimuli from within and outside the cell [ 94 ].…”
Section: Relationship Between CL − Channels and Em...mentioning
confidence: 99%
“…Furthermore, the application of cigarette smoke extract to human bronchial epithelial cells (16HBE) resulted in the induction of EMT. This was evidenced by increased vimentin expression and decreased E-cadherin expression, a phenomenon that was exacerbated by overexpression of TRPC1 [ 47 ]. Recently, a similar finding was observed by subjecting 16HBE cells to cyclic mechanical stretching to induce EMT, followed by both increased molecular and functional expression of TRPC1.…”
Section: Trp Channels In the Emtmentioning
confidence: 99%